Change of physical characteristics in Japanese elite junior divers - - longitudinal survey of 3 years— - Narita, T.; Kaneoka, K.; Okubo, Y.; Sakata, K.; Nomura, T. (Rigakuryoho Kagaku, 2012)
This study aimed to determine factors related to low back pain (LBP) from changes in the physical characteristics. [Subjects] Thirteen elite junior divers who were followed from 13 to 15 years old. [Methods] The change in each item between the ages of 13 and 15 years old were analyzed by one-way analysis of variance. [Results] Significant main effects were recognized between each age of height, weight, standing long jump, vertical jump, back muscle strength, sit-ups for 30 seconds, and handstand continuance time. [Conclusion] LBP possibly occurs owing to increase in weight after 15 years old.